2016
DOI: 10.1051/0004-6361/201628366
|View full text |Cite
|
Sign up to set email alerts
|

Joint signal extraction from galaxy clusters in X-ray and SZ surveys: A matched-filter approach

Abstract: The hot ionized gas of the intra-cluster medium emits thermal radiation in the X-ray band and also distorts the cosmic microwave radiation through the Sunyaev-Zel'dovich (SZ) effect. Combining these two complementary sources of information through innovative techniques can therefore potentially improve the cluster detection rate when compared to using only one of the probes. Our aim is to build such a joint X-ray-SZ analysis tool, which will allow us to detect fainter or more distant clusters while maintaining… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 38 publications
(56 reference statements)
0
37
0
Order By: Relevance
“…are the convolutions of the normalized cluster 2D spatial profiles (SZ and X-ray components, respectively) with the point spread function (PSF) of the instruments at the different frequencies; and the constant C is a geometrical factor that accounts for the different shapes of the SZ and X-ray 3D profiles (Eq. 25 of Tarrío et al (2016)). A more elaborated description of the filter can be found in Tarrío et al (2016) and Tarrío et al (2018).…”
Section: Joint Detection Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…are the convolutions of the normalized cluster 2D spatial profiles (SZ and X-ray components, respectively) with the point spread function (PSF) of the instruments at the different frequencies; and the constant C is a geometrical factor that accounts for the different shapes of the SZ and X-ray 3D profiles (Eq. 25 of Tarrío et al (2016)). A more elaborated description of the filter can be found in Tarrío et al (2016) and Tarrío et al (2018).…”
Section: Joint Detection Methodsmentioning
confidence: 98%
“…These profiles are not known in practice, so they need to be approximated by the theoretical profiles that best represent the clusters we want to detect. As in Tarrío et al (2016) and Tarrío et al (2018), we assume the generalized Navarro-Frenk-White (GNFW) profile (Nagai et al 2007) given by…”
Section: Joint Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Remazeilles et al (2013) propose a method which implements needlet decomposition, while in the recent work by Aghanim et al (2019) the authors apply suitable matched multi-filters (see e.g. Herranz et al 2002;Melin et al 2006;Tarrío et al 2016Tarrío et al , 2018 to data from Planck and from the Atacama Cosmology Telescope (Swetz et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Biffi, Dolag & Merloni 2018;Koulouridis et al 2018). Tarrío et al (2016) and Tarrio18 recently demonstrated that point source confusion can be reduced by a joint SZ and X-ray MMF analysis, using their very different spectral characteristics at microwave frequencies compared to the X-ray regime.…”
Section: Introductionmentioning
confidence: 99%